Isolation and Diagnosis of Gram-Negative Bacteria Causing Urinary Tract Infection from Transfusion Dependent Thalassemia and Study of Iron Acquisition Systems in Wasit, Iraq - Lubna Hussein Al-Abidy,; Salem Rheef Arian Al-Aidy, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Enterobacter cloacae complex, Klebsiella pneumoniae and E. coli belong to the family Enterobacteriaceae, and it is the most clinically pertinent species, also it causes both nosocomial and communities-acquired infections.Enterobacteriaceae are the main cause of these infections, but managing them has become more challenging due to the emergence of antibiotic resistance. The current study aimed to detect and diagnosed the causative agents of urinary tract infection UTI and their virulence genes for iron acquisition systems fepAandsitA genes in transfusion dependent thalassemia TDT in Wasit province Iraq 2024. One hundred seventy-three samples of urine were collected from Center of Blood Hereditary Diseases in Al-Kut Hospital from November 2023 to April 2024. Participants ranged from 6 months to 50 years. The results showed the diagnosis of 38 isolates of bacteria with an 7.9% n=3/38 prevalence ofE. cloacae complex, 13.3% n=5/38 ofKlebsiella pneumoniae and 23.7% n=9/38 for E. coli other bacteria were gram positive with prevalence 55.1% n=21/38 and the virulence genes for iron acquisition systems fepAandsitA were 64.7% n=11/17and 94.1% n=16/17 respectively